HONDMAN - D PILKEY
There's a new police officer on the scene! It's Hondman, crime-biting canine who is part dog, part man, and ALL HERO! When Ben the police dog and his cop companion are injured, a surgery changes the course of history, and Hondman is born. With the head of a dog and the body of a human, this heroic hound has a real nose for justice. But can he resist the call of the wild to answer the call of duty? Read this graphic novel and never stop laughing!
Kids